ENHANCEMENT OF DIGITAL BASED BATIK CRAFT PRODUCTS IN KEREK DISTRICT, TUBAN DISTRICT - Ratna Azis Prasetyo; Septi Ariadi; Udji Asiyah (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: Gedog batik weaving in Kerek District to become one of the regional superior products that started local development. The MEA era and the industrial revolution 4.0 provide challenges for these creative economies to survive amid increasingly fierce global competition. One of them is by comparison with the shift of consumer tastes. UMKM are those who become Gedog batik weavers who do not understand customer satisfaction at present, which emphasizes the value of goods purchased according to the value used first. UMKM also specializes in mastering digital technology as a marketing medium. Purpose: For this reason, community adoption activities for training and mentoring for batik UMKM participants in making branding to respond to customer convenience and increasing marketing of digital-based products for solutions that support partnerships. Methods: Community service methods are carried out by providing training and practicum on product branding and digital-based marketing for business entrepreneurs or batik artisans. Results: The result of these activity participants who initially did not understand the transition of consumers became aware of the need to do the branding of a digital-based product and marketing. Conclusion: Partners get increased knowledge and skills in digital-based batik marketing to respond to shifting consumer tastes.